More Nights than Days : A Survey of Writings of Child Genocide Survivors - Kiss, Yudit 1956- (Central European University Press, 2023)
This is a unique exploration of the experience of children who survived the Holocaust—including Roma and Sinti victims—and the genocides in Cambodia, Rwanda, and Bosnia. Children are among the principal victims of armed conflicts and slaughters; nonetheless, they perceive events through the prism of their unique perspective and have a different range of coping techniques than adults. This overview of the writings of ninety-one child survivors bears evidence to a wide range of human ruthlessness. The author presents little-known texts along with famous memoirs and autobiographical fiction, with abundant quotations. Many of these are not only compelling as historical testimony, but poetic, moving and stirring. Yudit Kiss has not written a historical study or literary criticism of the children’s books. She explores, instead, what the authors went through and what they felt and understood about their experience. Accessible and captivating, this volume presents a close-up, human-size dimension of destruction. The books written by child survivors also describe the resources and means that helped them to remain human even in the deepest well of inhumanity, offering precious lessons about resistance and resilience